Komodifikasi Kesedihan dalam Konten Berita Duka Public Figure di Aplikasi TikTok : Studi Kasus Pada Kabar Kematian Vidi Aldiano: abstract, introduction, theoretical basis, research method, research results and discussion, conclusion, bibliography - Tamara Marsya Safitri; Zalinggi Pramestha Wardhana (Kampus Akademik Publiser, 2026)
This study focuses on examining the commodification of grief in news content about the deaths of public figures on the TikTok app through a case study of the news of Vidi Aldiano’s death. The research focuses on how public grief is constructed, disseminated, and exploited as a digital commodity to garner audience attention, engagement, and economic profit on social media platforms. This study employs a qualitative descriptive method using a netnographic approach and Vincent Mosco’s theory of commodification to understand the relationship between emotional content, the audience, and digital platform mechanisms. The results indicate that tragic news, such as the death of a celebrity, can lead to increased engagement on accounts, which can yield commercial benefits. Public grief is not merely an emotional expression but is also commodified through content production and distribution practices oriented toward digital attention. This study concludes that TikTok serves as a space that highlights the transformation of collective emotions into economic value within the digital media ecosystem.